2013
DOI: 10.1002/maco.201307147
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surface pre‐treatments on corrosion behavior of cerium‐based conversion coatings on Al 7075‐T6

Abstract: Cerium‐based conversion coatings were deposited on Al 7075‐T6 and characterized to determine the effect of different surface pre‐treatments on the corrosion rate and surface morphology. The methods of potentiodynamic polarization and scanning electron microscopy were employed. The experimental results suggest that cerium‐based conversion coating is corrosion resistant in NaCl solution. Corrosion current decreased with alkaline cleaning and acid activation of aluminum surface before cerium oxide deposition. Alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…However, hexavalent chromium presents very high toxicity and has unusual environmental impact [17][18][19] . For this reason, an intense research effort is being undertaken to replace chromates by more environmentally friendly compounds.…”
Section: Introductionmentioning
confidence: 99%
“…However, hexavalent chromium presents very high toxicity and has unusual environmental impact [17][18][19] . For this reason, an intense research effort is being undertaken to replace chromates by more environmentally friendly compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the phosphating process is quite sensitive to the surface status of Mg substrate as other chemical conversion processes . The pretreatment process is especially important, and suitable pretreatments are effective method to further enhance the properties of chemical conversion films . Previous pretreatment investigations mainly focus on forming a thin surface layer to improve homogeneity and protect the Mg substrate from corrosion .…”
Section: Introductionmentioning
confidence: 99%
“…Lanthanide compounds have been applied as corrosion inhibitors for Al alloys . It is reported that cerium chloride (CeCl 3 ) is an effective inhibitor.…”
Section: Introductionmentioning
confidence: 99%